A RESPONSE OF THE "RESERVOIR-WELL" SYSTEM TO DISTANT EARTHQUAKES - E. M. Gorbunova; A. N. Besedina; I. A. Sanina; N. L. Konstantinovskaya (Геодинамика и тектонофизика, 2022)
The results of joint processing of hydrogeological and seismic data obtained at the Large-Scale Research Facilities "Mid-Latitude Geophysical Observation Complex "Mikhnevo" for a 12-year observation period are presented in the article. Responses of the "reservoir-well" system to the passage of seismic waves from distant earthquakes with magnitudes of 6.3-9.0, recorded at the epicentral distances from 1863 to 16507 km, have been identified in the database. Maximum values of groundwater level variations and ground velocity under seismic impact have been determined. The power-law dependence of the levels amplitudes of confined and weakly confined aquifers on the maximum vertical ground velocity has been established. A spectral analysis of 6-hour intervals (3 hours before and 3 hours after earthquakes) of seismic and hydrogeological data was performed. The frequencies corresponding to the maximum values of ground velocity and groundwater level variations were determined in the normalized spectra. The intervals within which the extremes of the hydrogeological responses are traced at background values of the ground velocity are identified in the low-frequency range. The amplitude-frequency characteristics of the "reservoir-well" systems differ under seismic impacts at epicentral distances up to 4901 km. The responses of the systems to earthquakes at epicentral distances of 11024-14026 km are similar.